Inflammatory markers predict episodes of wheezing during the first year of life in Bangladesh. (January 2016) - Burgess, Stacey L.; Lu, Miao; Ma, Jennie Z.; Naylor, Caitlin; Donowitz, Jeffrey R.; Kirkpatrick, Beth D.; Haque, Rashidul; Petri, William A.
Abstract: Background: Environmental factors that influence wheezing in early childhood in the developing world are not well understood and may be useful in predicting respiratory outcomes. Therefore, our objective was to determine the factors that can predict wheezing. Methods: Children from Dhaka, Bangladesh were recruited at birth and episodes of wheezing were measured alongside nutritional, immunological and socioeconomic factors over a one-year period. Poisson Regression with variable selection was utilized to determine what factors were associated with wheezing. Results: Elevated serum IL-10 (rate ratio (RR) = 1.51, 95% confidence interval (CI): 1.22–1.87), IL-1β (RR = 1.55, 95% CI: 1.26–1.93) C-reactive protein (CRP) (RR = 1.41, 95% CI: 1.03–1.93) in early life, and male gender (RR = 1.52, 95% CI: 1.27–1.82) predicted increased wheezing episodes. Conversely, increased fecal alpha-1-antitrypsin (RR = 0.87, 95% CI: 0.76–1.00) and family income (RR = 0.98, 95% CI: 0.97–0.99) were associated with a decreased number of episodes of wheezing. Conclusions: Systemic inflammation early in life, poverty, and male sex placed infants at risk of more episodes of wheezing during their first year of life. These results support the hypothesis that there is a link between inflammation in infancy and the development of respiratory illness later in life and provide specific biomarkers that can predict wheezing in a low-income country. Highlights: Factors that influence wheezing in early childhood in the developing world are poorly understood and were explored. Children from Bangladesh were recruited at birth and episodes of wheezing were measured over a one-year period. Wheezing was recorded alongside nutritional, immunological and socioeconomic factors. Systemic inflammation early in life, poverty, and male sex placed infants at risk of more episodes of wheezing.